Non-alcoholic fatty liver disease (NAFLD) and obesity in inflammatory bowel disease (IBD) patients in Gorgan - Sima Besharat; Farideh Sakhavi; Parsa Sookhtehsaraei; Mehrdad Teimoorian; Somayeh Livani; Alireza Norouzi; Taghi Amiriani (Babol University of Medical Sciences, 2024)
Background: According to the significance of extraintestinal symptoms in inflammatory bowel disease (IBD) patients and their connection with obesity, we aimed to investigate the prevalence of fatty liver in IBD patients of Sayyad Shirazi Hospital in Gorgan, Iran, in relation to obesity, anthropometric indicators and body image in these patients. Methods: Forty patients with IBD were recruited from all registered patients at the Golestan Research Center of Gastroenterology and Hepatology, following the specified inclusion and exclusion criteria. After obtaining written informed consent and filling in the questionnaire, the demographic and anthropometric indicators, and variables related to the disease were measured. The liver sonography was performed on all patients and graded by an expert radiologist. Data were analyzed using SPSS Version 16.0 statistical software at the significance level of 0.05. Results: We showed no significant difference between the distribution of demographic and anthropometric indicators in different groups of IBD patients. However, we demonstrated that the inappropriate values of HDL (0.004) and high values of LDL (0.015) were associated with fatty liver in IBD patients. Our findings also showed that NAFLD was significantly associated with overweight and obesity among IBD patients (P = 0.003). Conclusion: Our findings showed the epidemiological burden of NAFLD in IBD patients. Since fatty liver was associated with obesity, it is recommended that IBD patients be screened for risk factors associated with NAFLD to prevent liver disease.